2016
DOI: 10.1177/1934578x1601100324
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oil from the Fresh Fruits of Xylopia Laevigata and its Cytotoxic Evaluation

Abstract: The essential oil obtained by hydrodistillation from the fresh fruits of Xylopia laevigata was analyzed by gas chromatography using a flame ionization detector (GCFID) coupled to a mass spectrometer (GCMS). Monoterpenes predominated, forming 95.0% of the total essential oil. The major constituents identified were limonene (56.2%), -pinene (28.0%), and -pinene (5.5%). Cytotoxic activity against tumor cell lines and non-tumor cells was also investigated; however, neither the essential oil nor its major const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The in vitro cytotoxic activity of the EO from fresh fruits of Xylopia laevigata and its main constituents (limonene, α-pinene, and β-pinene) was evaluated against four tumor cell lines (mouse melanoma, human hepatocellular carcinoma, human promyelocytic leukemia, and chronic myelocytic leukemia) and non-tumor cells (human peripheral blood mononuclear cells). Neither the EO nor its major constituents showed cytotoxic activity (IC 50 > 25.0 µg•mL −1 ) [77].…”
Section: Antiproliferative and Cytotoxic Activitiesmentioning
confidence: 90%
“…The in vitro cytotoxic activity of the EO from fresh fruits of Xylopia laevigata and its main constituents (limonene, α-pinene, and β-pinene) was evaluated against four tumor cell lines (mouse melanoma, human hepatocellular carcinoma, human promyelocytic leukemia, and chronic myelocytic leukemia) and non-tumor cells (human peripheral blood mononuclear cells). Neither the EO nor its major constituents showed cytotoxic activity (IC 50 > 25.0 µg•mL −1 ) [77].…”
Section: Antiproliferative and Cytotoxic Activitiesmentioning
confidence: 90%
“…The chemical composition of essential oil from the leaves of X. laevigata included γ-muurolene, δ-cadinene, germacrene B, α-copaene, germacrene D, bicyclogermacrene and ( E )-caryophyllene as the major constituents [1,3,4,5]. The essential oil from its fresh fruits contained limonene, α-pinene and β-pinene as the major compounds [6]. Moreover, isoquinoline alkaloids were also found in its leaves [7].…”
Section: Introductionmentioning
confidence: 99%
“…Kouame et al [ 65 ] found that the EOs of the leaves and fruits of a sample of X. aethopica were also characterized by β-pinene (16.01–20.50%) and α-pinene (10.39–17.77%). Costa et al [ 66 ] identified high levels of α-pinene (28.00 ± 1.50%) and β-pinene (5.50 ± 0.10%) in the EO of the fruit of X. laevigata . Maia et al [ 67 ] stated that α- and β-pinene are the major components of the EO of X. cayennensis , with contents of 29.20% and 16.50%, respectively.…”
Section: Resultsmentioning
confidence: 99%